EVALUASI DAMPAK KEBIJAKAN ANGGARAN DANA BOS TERHADAP SEKTOR PENDIDIKAN - Rini, Amelya Putri Azizah; Muntahar, M. Fahri; Paola, Vicky Surya; Ramadhan, Syahrul Asri; Nursita, Lisa (Educational Leadership: Jurnal Manajemen Pendidikan, 2025)
This study aims to evaluate the impact of the School Operational Assistance Fund (BOS) budget policy on the education sector in Indonesia. The main focus of this study is to analyze the extent to which BOS Funds contribute to improving the quality of education, equalizing access, and the effectiveness of financing primary and secondary education. Using a descriptive approach with a literature study method (secondary research), data was collected from various sources such as ministry reports, scientific journals, and the results of studies by related institutions. The results of the study indicate that BOS Funds generally encourage increased participation in education for underprivileged students. However, a number of challenges are still faced, including delays in disbursement of funds, mismatch of allocation with actual needs, and weak supervision and financial reporting at the school level. On the other hand, the use of digital technology in BOS Fund reporting has begun to strengthen aspects of transparency and efficiency. This study recommends the importance of improving regulations, increasing school management capacity, and strengthening community involvement in supervision. BOS Funds need to be viewed as a strategic investment in developing fair and equitable human resources throughout Indonesia.